2006
DOI: 10.1051/gse:2006016
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic assessment of a Thyroglobulin marker for marbling in beef cattle

Abstract: -A meta-analysis was undertaken reporting on the association between a polymorphism in the Thyroglobulin gene (TG5) and marbling in beef cattle. A Bayesian hierarchical model was adopted, with alternative representations assessed through sensitivity analysis. Based on the overall posterior means and posterior probabilities, there is substantial support for an additive association between the TG5 marker and marbling. The marker effect was also assessed across various breed groups, with each group displaying a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A total of 469 QTL central locations are selected for 66 traits of pigs that are grouped into 14 clusters: abdominal fat (S1), backfat (average) thickness (S2), backfat at shoulder (S3), backfat at first rib (S4), backfat between 3rd and 4th rib (S5), backfat at 10th rib (S6), backfat at last rib (S7), backfat at last lumbar (S8), backfat weight (S9), fat percentage in carcass (S10), intermuscular fat percentage (S11), marbling (S12), fat androstenone level (13), and fatty acid composition (S14). et al, 2008), NPY (Sherman et al, 2008), and thyroglobulin (Wood et al, 2006) genes show significant effect on marbling, whereas FABP4 (Cho et al, 2008), IGF-2 (Sherman et al, 2008), and leptin (Buchanan et al, 2002;Schenkel et al, 2005) are associated with backfat thickness.…”
Section: Biology Of Adipocytes and Preadipocytesmentioning
confidence: 93%
“…A total of 469 QTL central locations are selected for 66 traits of pigs that are grouped into 14 clusters: abdominal fat (S1), backfat (average) thickness (S2), backfat at shoulder (S3), backfat at first rib (S4), backfat between 3rd and 4th rib (S5), backfat at 10th rib (S6), backfat at last rib (S7), backfat at last lumbar (S8), backfat weight (S9), fat percentage in carcass (S10), intermuscular fat percentage (S11), marbling (S12), fat androstenone level (13), and fatty acid composition (S14). et al, 2008), NPY (Sherman et al, 2008), and thyroglobulin (Wood et al, 2006) genes show significant effect on marbling, whereas FABP4 (Cho et al, 2008), IGF-2 (Sherman et al, 2008), and leptin (Buchanan et al, 2002;Schenkel et al, 2005) are associated with backfat thickness.…”
Section: Biology Of Adipocytes and Preadipocytesmentioning
confidence: 93%
“…45 found that the TG gene, which is located at 7.658 Mb on the chromosome, is significantly associated with marbling score in beef cattle. The association was further confirmed by the same group using another population of feedlot cattle 46. In contrast, Moore and colleagues 43 failed to confirm the association of polymorphisms in the TG gene with any lipid metabolism traits (backfat EBV).…”
Section: Qtl Detected On Bta14 In Beef Cattlementioning
confidence: 95%
“…The effect of a C/T single nucleotide polymorphism in the 5 ' -untranslated region of TG gene has been concluded to affect intramuscular fat content in cattle (Barendse 1999). High probability of positive association between the T allele of bovine TG gene and marbling was observed by Wood et al (2006). Thyroglobulin mainly affects the fat content of longissimus dorsi muscle (LD) (Thaller et al 2003).…”
Section: Introductionmentioning
confidence: 99%